Simultaneous biodegradation of tetrahydrofuran, 3-buten-1-ol and 1, 4-butanediol in real wastewater by a pilot high-rate UASB reactor. (September 2019) - Ni, Chen-Hua; Chang, Chia-Yuan; Lin, Yu-Chung; Lin, Justin Chun-Te
Abstract: A stream of wastewater from a synthetic-fibers manufacturing plant with high amount of tetrahydrofuran (THF), 3-buten-1-ol (BTO) and 1, 4-butanediol (BDO) results in high chemical oxygen demand (COD). A pilot high rate up-flow anaerobic sludge blanket (UASB) reactor, which recirculation rate was set at three times of feed flowrate, was conducted on-site and continuously run for 108 days. Volumeric organic loading rates were gradually adjusted from to 1.3 ± 0.2 to 21.5 ± 1.8 kg-COD·m −3 d −1 while corresponding COD in the influent increased from 1704 to the maximum up to 30700 mg L −1 . Average removals of COD were 75.8%, while temperature, pH, dissolved oxygen, and oxidation reduction potential were intensively monitored throughout the pilot study. Average THF removals of 89.1% and complete BTO removals showed successful biodegradation in the UASB reactor. Meanwhile, average BDO removals increased significantly from 43.2% to 95.8%. In addition, increasing of biomass and food-to-microorganism ratios were performed well by rational regressions. Anaerobic granules were also developed well to the final size of 3–4 mm. Moreover, total biogas production rates were increased by operation days. The main biogas component (CH4 ) increases five times while the other two (CO2 and N2 ) were kept steady. In general, start-up of the UASB for biodegradting real wastewaters containing high concentration of C4 chemicals was firstly demonstrated in the pilot study. Highlights: A high-rate UASB reactor was designed for real synthetic-fibers wastewater treatment. Simultaneous biodegradation of THF, BTO and BDO was first time conducted. Four key operational parameters (pH, temperature, DO and ORP) were monitored. Start-up of the pilot plant was performed and good performances were achieved. Main biogas produced in the pilot was identified as methane, and size of anaerobic granules were measured.